Clinical characteristics of inguinal bladder hernias and total extraperitoneal repair. Issue 3 (20th October 2020) - Hasegawa, Shinichiro; Ogino, Nobuo; Kanemura, Takashi; Sakao, Jun; Fujii, Hitoshi; Kikkawa, Hiroyuki; Tsujie, Masaki
Abstract: Introduction: Bladder hernia is relatively rare in cases of inguinal hernia. In some instances, bladder hernia may be treated as inguinal hernia if bladder prolapse is not recognized. Because of the rarity of inguinal bladder hernias, there are no related detailed reports from studies performed at a single institution. In our hospital, patients with suspected inguinal hernia undergo CT in the prone position, enabling the diagnosis of bladder hernia preoperatively. This study aimed to clarify the clinical characteristics of inguinal bladder hernias and consider noteworthy points in their laparoscopic treatment. Methods: This retrospective analysis included data from 32 consecutive patients with bladder hernia in 1126 patients with inguinal hernia. In each patient, the lengths of the hernial orifice and prolapsed bladder were measured on the CT images and intraoperatively. Totally extraperitoneal (TEP) repair was performed in all patients, who were then followed for 1 year postoperatively. Results: Inguinal bladder hernia was detected on CT in 32 of 1126 patients (2.8%). Among them, only five (15.6%) had urological symptoms such as pollakiuria or the sensation of residual urine. The 32 patients were classified into three groups according to hernia subtype: intraperitoneal (n = 12, 37.5%), para‐peritoneal (n = 15, 46.9%), and extraperitoneal (n = 5, 15.6%). The prolapsed bladder of the extraperitoneal type was significantly shorter than that of the other subtypes. The prolapsed bladders were directly identified in the extraperitoneal space and repaired safely with TEP. One recurrence (3.1%) occurred 2 months postoperatively. Conclusion: Preoperative CT and TEP are useful for the definitive diagnosis and treatment of inguinal bladder hernia.